Neural Mechanisms of Post-error Adjustments of Decision Policy in Parietal Cortex - Purcell, Braden A. (Neuron, 2016)
Humans often slow down after mistakes (post-error slowing, PES), but the neural mechanism and adaptive role of PES remains controversial. We studied changes in the neural mechanisms of decision-making after errors in humans and monkeys that performed a motion-direction discrimination task. We found that PES is mediated by two factors: a reduction in sensitivity to sensory information and an increase in the decision bound. Both effects are implemented through dynamic changes in the decision-making process. Neuronal responses in the monkey lateral intraparietal area (LIP) revealed that bound changes are implemented by decreasing an evidence-independent urgency signal. They also revealed a reduction in the rate of evidence accumulation, reflecting reduced sensitivity. These changes in the bound and sensitivity provide a quantitative account of choices and response times. We suggest that PES reflects an adaptive increase of decision bound in anticipation of maladaptive reductions in sensitivity to incoming evidence.